Intrapartum sonographic weight estimation - Faschingbauer, Florian; Dammer, U.; Raabe, E.; Schneider, M.; Faschingbauer, Cornelia; Schmid, M.; Schild, R. L.; Beckmann, Matthias; Kehl, Sven; Mayr, Andreas (Archives of Gynecology and Obstetrics, 2015)
To evaluate the accuracy of intrapartum sonographic weight estimation (WE).This retrospective, cross-sectional study included 1958 singleton pregnancies. Inclusion criteria were singleton pregnancy with cephalic presentation, vaginal delivery and ultrasound examination with complete biometric parameters performed on the day of delivery during the latent or active phase of labor, and absence of chromosomal or structural anomalies. The accuracy of intrapartum WE was compared to a control group of fetuses delivered by primary cesarean section at our perinatal center and an ultrasound examination with complete biometric parameters performed within 3 days before delivery (n = 392). Otherwise, the same inclusion criteria as in the study group were applied. The accuracy of WE was compared between five commonly applied formulas using means of percentage errors (MPE), medians of absolute percentage errors (MAPE), and proportions of estimates within 10 % of actual birth weight.In the whole study group, all equations showed a systematic underestimation of fetal weight (negative MPEs). Overall, best MAPE and MPE values were found with the Hadlock II formula, using BPD, AC and FL as biometric parameters (Hadlock II, MPE: -1.28; MAPE: 6.52). MPEs differed significantly between WE in the study and control group for all evaluated formulas: in the control group, either no systematic error (Hadlock III, IV and V) or a significant overestimation (Hadlock I, II) was found. Regarding MAPEs, application of the Hadlock III (HC, AC, FL) and V (AC) formula resulted in significant lower values in the control group (Hadlock III, MAPE: 7.48 vs. 5.95, p = 0.0008 and Hadlock V, MAPE: 8.79 vs. 7.52, p = 0.0085). No significant differences were found for the other equations.A systematic underestimation of fetal weight has to be taken into account in sonographic WE performed intrapartum. Overall, the best results can be achieved with WE formulas using the BPD as the only head measurement.
EVALuna2:5506